2019
DOI: 10.3390/ma12162570
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Different Pretreatments on the Structure and Hydrolysis Behavior of Bamboo: A Comparative Study

Abstract: In the present study, three pretreatments of sodium hydroxide (NaOH), sulfuric acid (H2SO4), and glycerin were employed with bamboo fibers at two different temperatures of 117 °C and 135 °C, respectively. The chemical composition and structural characterization of the pretreated bamboo fibers were comparatively studied using spectroscopic and wet chemistry methods. Furthermore, the comparative hydrolysis behaviors of pretreated bamboo were studied due to the synergistic interaction between cellulases and xylan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(4 citation statements)
references
References 33 publications
1
3
0
Order By: Relevance
“…Similar results have been reported by Ji et al, who observed that the cellulose content (72.4%) of acid pretreated hemp biomass was increased than untreated hemp biomass [48]. According to Qi et al, chemical pretreatment of bamboo using acid and alkali exhibited the highest cellulose content and lowest lignin and extractive content [49].…”
Section: Pretreatments Of Flaxseed Mealsupporting
confidence: 86%
“…Similar results have been reported by Ji et al, who observed that the cellulose content (72.4%) of acid pretreated hemp biomass was increased than untreated hemp biomass [48]. According to Qi et al, chemical pretreatment of bamboo using acid and alkali exhibited the highest cellulose content and lowest lignin and extractive content [49].…”
Section: Pretreatments Of Flaxseed Mealsupporting
confidence: 86%
“…The peak at 1742 cm −1 and 1510 cm −1 corresponded to the C-O stretching vibrations of hemicellulose, and the C=C vibrations in lignin were not displayed in the observed spectra of extracted cellulose and commercial cellulose samples. The absence of absorption peaks at the aforementioned bands revealed that hemicellulose and lignin impurities were completely removed [33,34]. The O-H bending vibration owing to the moisture absorption of cellulose denotes the peaks at wavenumbers of 1636-1612 cm −1 for all samples.…”
Section: Fourier Transform Infrared (Ftir) Of Cellulose Samples Extra...mentioning
confidence: 93%
“…Ammonia pretreatment causes structural changes in the biomass by breaking the lignin-carbohydrate ester bonds and partial removal of extractives (Bensah and Mensah, 2018). Unlike extractives, the ash content increases after glycerol and ammonia pretreatment (Cha et al, 2014;Qi et al, 2019).…”
Section: Introductionmentioning
confidence: 99%